Evaluation of Apelin and Apelin Receptor Level in the Primary Tumor and Serum of Colorectal Cancer Patients - Marta Podgórska (Journal of Clinical Medicine, 2019)
Colorectal cancer is the second deadliest tumor, which has a positive correlation with obesity which led to increasing interest in the relationship between adipokines and cancer progression. Apelin is a secreted peptide involved in regulation of tumor progression and invasiveness. In this study, we examined apelin and apelin receptor expression level in colorectal cancer. Apelin, and its receptor mRNA, and protein expression levels were measured in tumor tissue of 56 surgically treated colorectal adenocarcinoma (CRC) patients. We also analyzed apelin and apelin receptor protein levels in sera of 56 CRC patients and 27 healthy controls. The mRNA and protein level of this peptide and its receptor was higher in tumors than that in control tissue. Serum levels of apelin and apelin receptor were increased in CRC patients in comparison to controls. The concentration of serum apelin level significantly increased in individuals with lymph node and distant metastasis. Obtained results suggest that apelin could be an important factor in progression of colorectal carcinoma.